Calculation Analysis Of Cost Of Cost Of Cocoa Production In PT. Tanah Mas Celebes Indah North Kolaka District - Khaerun Nisa (JEKAMI Journal of Accounting, 2022)
The purpose of this study was to determine the process of calculating the cost of goods sold chocolate products in maximizing profit at PT. Tanah Mas Celebes Indah Branch of North Kolaka Regency.In this study using a quantitative descriptive approach with data collection techniques using primary data obtained directly from the company such as interview data and data in the from of information on company production costs for one month. The results showed that the calculation of the cost of goods sold at PT. Tanah Mas Celebes Indah, in maximizing profit, carries out the process of minimizing all production costs to reduce expenses and maximize profits, such as purchasing quality cocoa pods at low prices from farmers or using machines that are cheaper to maintain compared to using human labor in the processing of cocoa pods turn brown.